EFFECT OF OSTEOPOROSIS ON ORAL HEALTH IN PERIMENOPAUSAL WOMEN - Kazakova N.N. (Scholar Express Journals, 2024)
Osteoporosis with its multifaceted effects on the body is a problem for all doctors, including dentists. This disease is a common disease not only in Europe and America, but also in Asia. (Rozhinskaya L.Ya., 2007; Mulligan R., Sobel S., 2005). It is known that the violation of the structure and function of the alveolar process in general osteoporosis has an extremely negative effect on periodontal tissues. (Povoroznyuk V.V. et al., 2003; Mukhamedzhanova L.R., 2005; Shtorina G.B. et al., 2005), as a result, this cause, along with other negative factors, leads to early loss of teeth
Keywords: Osteoporosis; Dentistry; Menopausal Age